KONSEP DIRI PEREMPUAN MARGINAL - Purwanti, Yanti Dewi; Koentjoro, -; Purnamaningsih, Esti Hayu (Faculty of Psychology, Universitas Gadjah Mada, 2000)
The aim of this study was to make an objective description about self concept of â€œPerempuan Marginalâ€ (women in marginal social and economic status) by concerning the rearing environment characterization. The hypotesis was there is difference self-concept related in the rearing environmen. Data was collected from 77 subjects, 34 subjects upbringing by original family, 34 subject were reared in orphanage and the rest 9 subjects were taken from street children community. Data was gathered by Q-Sort test modification, observation, interview and also by Focus Group Discussion. Result shows that female teenagers from orphanage have the highest selfconcept, meanwhile female teenagers from street children community have the lowest self-concept. Keywords: self-concept; â€œperempuan marginalâ€; teenager